Gross rearrangements of the MECP2 gene are found in both classical and atypical Rett syndrome patients. Issue 5 (23rd September 2005) - Archer, H L; Whatley, S D; Evans, J C; Ravine, D; Huppke, P; Kerr, A; Bunyan, D; Kerr, B; Sweeney, E; Davies, S J; Reardon, W; Horn, J; et al.
Abstract : MECP2 mutations are identifiable in ∼80% of classic Rett syndrome (RTT), but less frequently in atypical RTT. We recruited 110 patients who fulfilled the diagnostic criteria for Rett syndrome and were referred to Cardiff for molecular analysis, but in whom an MECP2 mutation was not identifiable. Dosage analysis of MECP2 was carried out using multiplex ligation dependent probe amplification or quantitative fluorescent PCR. Large deletions were identified in 37.8% (14/37) of classic and 7.5% (4/53) of atypical RTT patients. Most large deletions contained a breakpoint in the deletion prone region of exon 4. The clinical phenotype was ascertained in all 18 of the deleted cases and in four further cases with large deletions identified in Goettingen. Five patients with large deletions had additional congenital anomalies, which was significantly more than in RTT patients with other MECP2 mutations (2/193; p<0.0001). Quantitative analysis should be included in molecular diagnostic strategies in both classic and atypical RTT.